PENYESUAIAN DIRI SISWA MAN DITINJAU DARI KECERDASAN EMOSIONALNYA - A. S. Nwita dan Martina Winami (Jurnal Psikologi, 2007)
One hundred md three students grade 10 and II from a Moslem school participated on this study in order to understand the relationship between the emotional intelligence and social adjustment The former variable performed as the independent variable and was measured through the Emotional Intelligence Scale with 37 items. The dependent variable was the student's social adjustment and was measured through the Social Adjustment Seale with 36 items. The significant correlation of those variables were r = .636, p< .01. and the emotional intelligence would lie able to predict the 40.4% occurrence of social adjustment. The religious school environment may explain the high emotional intelligence among students. Everyday they have to learn on how to manage their behaviors that shall be appropriate with the Moslem regulation.